2021
DOI: 10.34133/2021/9829374
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Efficient Red Perovskite Light-Emitting Diodes Based on Ca 2+ -Doped CsPbI 3 Nanocrystals

Abstract: α-CsPbI3 nanocrystals (NCs) with poor stability prevent their wide applications in optoelectronic fields. Ca2+ (1.00 Å) as a new B-site doping ion can successfully boost CsPbI3 NC performance with both improved phase stability and optoelectronic properties. With a Ca2+/Pb2+ ratio of 0.40%, both phase and photoluminescence (PL) stability could be greatly enhanced. Facilitated by increased tolerance factor, the cubic phase of its solid film could be maintained after 58 days in ambient condition or 4 h accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…SA has a short carbon chain and a conjugated aromatic ring, for which conductivity should be much higher than for classic ligands. The hole migration rates were estimated by fitting the space-charge-limited-current region with Child’s law where ε 0 is the vacuum permittivity; ε is the average relative dielectric constant of CsPbBr 3 (ε ≈ 22). , L is the thickness of the perovskite film; and J , μ, and V are the measured current density, carrier migration rates, and applied voltage, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SA has a short carbon chain and a conjugated aromatic ring, for which conductivity should be much higher than for classic ligands. The hole migration rates were estimated by fitting the space-charge-limited-current region with Child’s law where ε 0 is the vacuum permittivity; ε is the average relative dielectric constant of CsPbBr 3 (ε ≈ 22). , L is the thickness of the perovskite film; and J , μ, and V are the measured current density, carrier migration rates, and applied voltage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The hole migration rates were estimated by fitting the space-charge-limited-current region with Child's law. 41 εε μ…”
Section: Resultsmentioning
confidence: 99%
“…Lead halide perovskite materials have been extensively studied in light-emitting diodes (LEDs) due to their high photoluminescence quantum yields (PLQYs) with tunable wavelengths and gradually improved stability. 1–10 Compared to all-inorganic lead halides, organic–inorganic hybrid lead halides exhibit tunable optical and physical properties because of the flexible structure and size of their organic molecules. 11–15 Several recent studies have demonstrated that MAPbX 3 and FAPbX 3 have high PLQYs, and narrow full width at half maxima (FWHMs).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hot-injection and room temperature recrystallization methods have been well developed to synthesize high-quality perovskite NCs. However, both methods suffered from the problem of solvent toxicity. Although one type of no-solvent method, e.g., the mechanochemical method, , has been developed to avoid toxic solvents, the perovskite NCs acquired with this approach have relatively low photoluminescence quantum yields (PLQYs) and are hardly solution-processable. Along with the surge of a global green wave, reducing or eliminating the use of toxic solvents is imperative and developing high-performance and green solution-processable perovskite NCs is desired.…”
Section: Introductionmentioning
confidence: 99%